Penggunaan Media Visual dalam Meningkatkan Pemahaman Siswa Terhadap Materi Sejarah di Kelas VIII SMP Negeri 3 Duhiada’a - Jailani M. Biki; Resmiyati Yunus; Iis Husnul Hotimah (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study investigates the role of visual media in enhancing students’ understanding of historical content in Social Studies among Grade VIII students at SMP Negeri 3 Duhiadaa. Employing a qualitative descriptive approach within a naturalistic framework, the research explores learning dynamics through participatory observation, in-depth interviews, and documentation. The findings reveal a progressive transformation in students’ comprehension, marked by improved conceptual articulation, increased engagement, and more active participation during the learning process. Visual media functioned as a cognitive mediator, enabling students to reconstruct abstract historical concepts into meaningful and structured knowledge. The integration of visual elements such as infographics, videos, and digital maps facilitated dual-channel information processing, strengthening memory retention and interpretative abilities. Furthermore, the study identifies the emergence of critical thinking patterns through cognitive conflict and reflective learning experiences. The results also highlight the importance of aligning instructional design with students’ visual learning tendencies to optimize learning outcomes. Theoretically, this research contributes to the development of a conceptual model of visual-based historical learning, while practically offering pedagogical insights for designing more participatory and cognitively effective classroom environments in contemporary education.